2007
DOI: 10.1038/sj.pcan.4501017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic changes in pT2 and pT3 prostate cancer detected by comparative genomic hybridization

Abstract: Prostate-specific antigen (PSA) screening has led to a remarkable increase in prostate cancer cases undergoing operative therapy. Over half of patients with locally advanced cancer (^pT3) develop rising PSA levels (biochemical failure) within 10 years. It is very difficult to predict which patients will progress rapidly to advanced disease following biochemical failure (BF). Therefore, a more useful prognostic factor is needed to suggest the most appropriate therapies for each patient. To determine chromosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…This data is in agreement with previous studies of prostate cancer in American [15] and Japanese populations [12] . Previous studies of prostate cancer in Japanese patients suggest that LOH of 13q14 is more frequent in metastatic foci than in primary tumors [18] , and losses of 13q14-31 are observed more frequently in pT3 tumors than in pT2 tumors [12] . These previous results, together with our data, may indicate that loss of 13q14 plays an important role in tumor progression of prostate cancer.…”
Section: Discussionsupporting
confidence: 83%
“…This data is in agreement with previous studies of prostate cancer in American [15] and Japanese populations [12] . Previous studies of prostate cancer in Japanese patients suggest that LOH of 13q14 is more frequent in metastatic foci than in primary tumors [18] , and losses of 13q14-31 are observed more frequently in pT3 tumors than in pT2 tumors [12] . These previous results, together with our data, may indicate that loss of 13q14 plays an important role in tumor progression of prostate cancer.…”
Section: Discussionsupporting
confidence: 83%
“…Both deletions 29 and amplifications 30 of 17q21 have been described in prostate-cancer specimens. However, such analyses need to be performed in tumors from known HOXB13 G84E carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Array‐based genome‐wide gene expression analysis and DNA copy number analysis have shown tumor‐suppressive genes, such as PTEN , ATBF , KLF5 and KLF6 , and oncogenic genes, such as c‐MYC , AR and TEMPRESS/ERG , that contribute to PCa oncogenesis . Recent high‐resolution array of comparative genomic hybridization (array‐CGH) studies have identified several chromosomal alterations using PCa cell lines and primary tissues . Among these chromosomal deletion or amplification regions, novel cancer‐related genes or miRNA might exist.…”
Section: Chromosome Mapping Of Aberrantly Expressed Mirna In Pcamentioning
confidence: 99%
“…29,30 Recent high-resolution array of comparative genomic hybridization (array-CGH) studies have identified several chromosomal alterations using PCa cell lines and primary tissues. [31][32][33] Among these chromosomal deletion or amplification regions, novel cancer-related genes or miRNA might exist.…”
Section: Chromosome Mapping Of Aberrantly Expressed Mirna In Pcamentioning
confidence: 99%